International criminal jurisdiction : whose law must we obey? - Gallant, Kenneth S., 1951- (New York, NY : Oxford University Press, 2022)
"Whose law must I obey? This question is so basic to our legal obligations that it ought to be easy. Specifically, a person considering an action ought to be able to answer this question by the use of law-like rules. This ought to be particularly true of criminal law, which will be the principal focus of this book. Actually, this question is partially unanswerable in the world as it exists today. Whether by accident or design, the current structure and content of law-national and international-sometimes prevents persons (natural or juridical) from being able to answer the question fully at the time of action"--
The question of jurisdiction -- The national and international law of criminal jurisdiction : structure and sources -- The standard model of criminal jurisdiction : introduction and general issues -- The territorial principle -- The nationality principle -- The protective principle -- The passive personality principle -- The universality principle -- Challenges to the standard model -- Sumary : the international law of criminal jurisdiction today, its sources, and the individual's place in it -- Jurisdiction, individual choice, and the principle of guilt (schuldprinzip) : a substantive criminal law approach -- Outsiders' responsibility to answer for crime : an approach from legal philosophy -- Jurisdiction and legality -- Conclusion : where might we go from here?
Includes bibliographical references (pages 719-736) and index.
Keywords: Criminal jurisdiction; Transnational crime -- Law and legislation